PENERAPAN KURIKULUM 2013 (K-13) PADA MATA PELAJARAN SEJARAH DI MA MUHAMMADIYAH PEKANBARU - Didik Ahmadi; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstarct: The purpose of this study was to determine the planning, implementation, and evaluation of 2013 curriculum-based learning in history subjects at MA Muhammadiyah Pekanbaru. The subject of this study was a history subject teacher of one person and the object of research was the application of the 2013 Curriculum (K-13) to the history subjects at MA Muhammadiyah Pekanbaru. In collecting data, observation, interview and documentation techniques are needed. To analyze the data obtained used descriptive qualitative analysis techniques and percentages. After analyzing the data it can be concluded that, planning is categorized as very good, with a percentage located between 76% -100%, precisely at 100%, implementation is categorized as very good, with a percentage located between 76% -100%, precisely at 93.75%, and Evaluation is categorized as good, with a percentage between 51% -75%, precisely at 54.54%. Key Words: Implementation, 2013 Curriculum